1949
DOI: 10.1021/ja01172a098
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction of Substituted Nitrobenzenes at the Dropping Mercury Cathode

Abstract: Substituted nitrobenzenes were among the first organic compounds to be investigated using the polarographic technique. The early work was performed by the Japanese, Shikata and his co-workers, and from this work Shikata and Tachi3 formulated the "electronegativity rule of reduction potentials," i. e., that organic compounds are more easily reduced as more electronegative groups are substituted in the same molecule.These investigators measured the reduction potentials by the tangent method us. the normal calome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1950
1950
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…It could be seen that there was a distinct peak appearing at the −500 mV (SCE) region, and the cathodic current at this potential increased with the increase in the concentration of nitrobenzene. Thus, the cathodic peak current at −500 mV was associated with the reduction of nitrobenzene; this was in agreement with electroreduction potential reported for this reactant 31…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It could be seen that there was a distinct peak appearing at the −500 mV (SCE) region, and the cathodic current at this potential increased with the increase in the concentration of nitrobenzene. Thus, the cathodic peak current at −500 mV was associated with the reduction of nitrobenzene; this was in agreement with electroreduction potential reported for this reactant 31…”
Section: Resultssupporting
confidence: 90%
“…Thus, the cathodic peak current at À500 mV was associated with the reduction of nitrobenzene; this was in agreement with electroreduction potential reported for this reactant. 31…”
Section: Electrocatalytic Reduction Of Nitrobenzenementioning
confidence: 99%
“…It could be seen that there was a distinct peak appearing at the −500 mV (SCE) region and the cathodic current at this potential increased with the increase in concentration of nitrobenzene. Thus, the cathodic peak current at −500 mV is associated with the reduction of nitrobenzene, which is in agreement with electro‐reduction potential reported for this reactant 41–43…”
Section: Resultssupporting
confidence: 90%
“…The substituents make the reduction of nitrobenzene more difficult in the following order: nitro > carboxyl > chloro > methyl. Nitro and carboxyl show a greater effect in the ortho and para position than in the meta, whereas chlorine and methyl which increase the electron density at the ortho and para positions make the meta more easily reduced (3). The values reported by these investigators (3) differ from those reported by Pearson {31) by 0.25 to 0.35 volt.…”
Section: O (X)mentioning
confidence: 71%